DO FUND MANAGERS KEEP THEIR PROMISES?: THE CASE OF MALAYSIAN ISLAMIC EQUITY FUNDS - Ayu Syafitri, Feranda
Islamic Finance in Malaysia has been growing significantly for the past decades. Many financal products in Malaysia today, including but not limited to the Islamic Banking and Investment Products have adopted and inserted the Islamic law or best referred as shari’ah law in their business exercise. Shari’ah law itself defines whether an object is halal (permissible) or haram (non-permissible) based on the Holy Quran, the practice of Prophet Muhammad SAW and the discussion of Muslim’s scholar (ijtima’). Shari’ah law in investment products protects those from riba’(excessive overcharging), masyir (speculative investment), and gharar (excessive risk). This research will focus on the Shari’ah investment product of equity fund family which is the Islamic Equity Fund (IEF) in Malaysia. For IEFs to be able to refer as Shari’ah compliant, they have to comply with specific Shari’ah screening criteria which often include business activity screening that will limit firms from being expose to impermissible business activity and financial screening which include liquidity ratio, interest ratio, and debt ratio. These screening can be found in IEFs’ respective prospectus if they decide to disclose it. Thus, the objective of this research will be to examine the degree of shari’ah compliance of Malaysian IEFs based on their respective fund’s own shari’ah screening method. However, due to the variety of screening criteria each fund has, comparison of compliance degree using the Morgan-Stanley Capital International (MSCI) Islamic index which is known as one of the most rigorous Shari’ah screening methodology. This is also to see whether or not IEFs that pass the MSCI index-given the strict and stringent status of this measurement- tend to also pass its own shari’ah screening index. v The compliance of IEFs cannot be separated from the role of Shari’ah Advisory Board (SAB). SAB is the governance body of IEF whose role is to ensure the shari’ah compliance of IEFs and to state whether IEFs is comply or not. Therefore, we will include some characteristics of Shari’ah Advisory Board (SAB) which are: SAB size; SAB competence; and SAB cross-board membership in the linear regression model to see whether there is any linear relationship of these characteristics to the degree of IEFs’ Shari’ah compliance. The implication of this research is that investors who seek for the shari’ah compliance investment have to be mindful about the compliance risk as we found that the average compliance degree of IEF’s based on its own screening criteria is only 57.94 percent while based on the MSCI Islamic index is 53.78 percent. Among the screening attribute, debt ratio appears to be the most restrictive as there are only about 60 percent holdings comply to the benchmark given. From the linear regression analysis, this research proved that there is no significant linear relation between SAB characteristics and IEF’s Shari’ah degree compliance, however, another finding shows that IEFs with less Malaysian holdings has higher shari’ah compliance degree based on the MSCI Islamic index. And finally, this research is able to prove that IEFs’ which comply to the MSCI Islamic index will more likely to comply with their own screening index showing SABs are more likely to adopt a more lenient Shari’ah screening criteria.